2022
DOI: 10.3389/fimmu.2022.1038570
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and validation of a carbohydrate metabolism-related gene signature for prognostic model and immune response in acute myeloid leukemia

Abstract: IntroductionThe heterogeneity of treatment response in acute myeloid leukemia (AML) patients poses great challenges for risk scoring and treatment stratification. Carbohydrate metabolism plays a crucial role in response to therapy in AML. In this multicohort study, we investigated whether carbohydrate metabolism related genes (CRGs) could improve prognostic classification and predict response of immunity and treatment in AML patients.MethodsUsing univariate regression and LASSO-Cox stepwise regression analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…A Chinese group generated a prognosis risk score with a panel of six serum glucose metabolism markers, which displayed an independent prognostic value in cytogenetically normal AML patients [3]. Moreover, the consistency and accuracy of a carbohydrate-metabolismrelated gene prognostic signature on the predictive performance of AML survival was validated using GEO cohorts and the authors' own cohort [24]. Another group recently developed a distinct six-lipid-metabolism-related-gene prognostic risk signature for AML [25].…”
Section: Discussionmentioning
confidence: 99%
“…A Chinese group generated a prognosis risk score with a panel of six serum glucose metabolism markers, which displayed an independent prognostic value in cytogenetically normal AML patients [3]. Moreover, the consistency and accuracy of a carbohydrate-metabolismrelated gene prognostic signature on the predictive performance of AML survival was validated using GEO cohorts and the authors' own cohort [24]. Another group recently developed a distinct six-lipid-metabolism-related-gene prognostic risk signature for AML [25].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, it is a great challenge to early identify stratification of risk in patients with ccRCC and provide accurate clinical individualized therapeutic. With the development of sequencing, mounting evidences indicated that prognostic signature based on combining genes expression and clinical feature could be used as a new biomarker to optimize risk stratification, predict clinical prognosis and evaluate response to clinical treatment (7)(8)(9). These novel prognostic signatures could help doctors implemented individualized therapy to extend the survival of patients.…”
Section: Introductionmentioning
confidence: 99%